Two-Cell Spheroid Angiogenesis Assay System Using Both Endothelial Colony Forming Cells and Mesenchymal Stem Cells - Shah, Sajita (Biomol Ther (Seoul), 2018)
Most angiogenesis assays are performed using endothelial cells. However, blood vessels are composed of two cell types: endothelial cells and pericytes. Thus, co-culture of two vascular cells should be employed to evaluate angiogenic properties. Here, we developed an in vitro 3-dimensional angiogenesis assay system using spheroids formed by two human vascular precursors: endothelial colony forming cells (ECFCs) and mesenchymal stem cells (MSCs). ECFCs, MSCs, or ECFCs+MSCs were cultured to form spheroids. Sprout formation from each spheroid was observed for 24 h by real-time cell recorder. Sprout number and length were higher in ECFC+MSC spheroids than ECFC-only spheroids. No sprouts were observed in MSC-only spheroids. Sprout formation by ECFC spheroids was increased by treatment with vascular endothelial growth factor (VEGF) or combination of VEGF and fibroblast growth factor-2 (FGF-2). Interestingly, there was no further increase in sprout formation by ECFC+MSC spheroids in response to VEGF or VEGF+FGF-2, suggesting that MSCs stimulate sprout formation by ECFCs. Immuno-fluorescent labeling technique revealed that MSCs surrounded ECFC-mediated sprout structures. We tested vatalanib, VEGF inhibitor, using ECFC and ECFC+MSC spheroids. Vatalanib significantly inhibited sprout formation in both spheroids. Of note, the IC(50) of vatalanib in ECFC+MSC spheroids at 24 h was 4.0 ± 0.40 μM, which are more correlated with the data of previous animal studies when compared with ECFC spheroids (0.2 ± 0.03 μM). These results suggest that ECFC+MSC spheroids generate physiologically relevant sprout structures composed of two types of vascular cells, and will be an effective pre-clinical in vitro assay model to evaluate pro- or anti-angiogenic property.